Factors Associated with 0-28 Day Neonatal Mortality in Central Aceh Regency - Amirah, Asriwati; Nadapdap, Thomson P; Suryani, Suryani (International Journal Papier Advance and Scientific Review, 2021)
This study aims to determine the factors associated with neonatal mortality 0-28 days in Central Aceh District in 2020. This research is a quantitative study with a case control research design and uses a retrospective approach. The study population was all mothers giving birth whose babies died at the age of 0-28 days from January to December 2020. The sample in this study was 120 respondents consisting of 60 cases and 60 controls. The sampling technique used was total sampling. Data analysis using chi square test and multiple logistic regression test. The results of the bivariate analysis using the chi square test showed that there were 2 variables that were significantly related to neonatal mortality, namely the maternal age variable with p value = 0.012 and the pregnancy examination variable with p value = 0.047. The results of multivariate analysis with multiple logistic regression test showed that there were 3 variables that influenced neonatal mortality, namely the maternal age variable with a p value of 0.001, the birth spacing variable with a p value of 0.018 and the pregnancy examination variable with a p value of 0.018, while the most dominant variable affecting the incidence of death Neonatal age is the variable of maternal age with an OR value of 4.397.